Targeting transglutaminase 2 partially restores extracellular matrix structure but not alveolar architecture in experimental bronchopulmonary dysplasia. (7th July 2018) - Mižíková, Ivana; Pfeffer, Tilman; Nardiello, Claudio; Surate Solaligue, David E.; Steenbock, Heiko; Tatsukawa, Hideki; Silva, Diogo M.; Vadász, István; Herold, Susanne; Pease, Richard J.; Iismaa, Siiri E.; Hitomi, Kiyotaka; et al.
Abstract : The generation, maturation and remodelling of the extracellular matrix (ECM) are essential for the formation of alveoli during lung development. Alveoli formation is disturbed in preterm infants that develop bronchopulmonary dysplasia (BPD), where collagen fibres are malformed, and perturbations to lung ECM structures may underlie BPD pathogenesis. Malformed ECM structures might result from abnormal protein cross‐linking, in part attributable to the increased expression and activity of transglutaminase 2 (TGM2) that have been noted in affected patient lungs, as well as in hyperoxia‐based BPD animal models. The objective of the present study was to assess whether TGM2 plays a causal role in normal and aberrant lung alveolarization. Targeted deletion of Tgm2 in C57BL/6J mice increased septal thickness and reduced gas‐exchange surface area in otherwise normally developing lungs. During aberrant lung alveolarization that occurred under hyperoxic conditions, collagen structures in Tgm2 −/− mice were partially protected from the impact of hyperoxia, where normal dihydroxylysinonorleucine and hydroxylysylpiridinoline collagen cross‐link abundance was restored; however, the lung alveolar architecture remained abnormal. Inhibition of transglutaminases (including TGM2) with cysteamine appreciably reduced transglutaminase activity in vivo, as assessed by N ε ‐(γ‐l ‐glutamyl)‐l ‐lysine abundance and TGM catalytic activity, and restored normal dihydroxylysinonorleucine and hydroxylysylpiridinoline collagen cross‐link abundance under pathological conditions. Furthermore, a moderate improvement in alveoli size and gas‐exchange surface density was noted in cysteamine‐treated mouse lungs in which BPD was modelled. These data indicate that TGM2 plays a role in normal lung alveolarization, and contributes to the formation of aberrant ECM structures during disordered lung alveolarization. Abstract : Transglutaminases ('nature's glues') undertake protein cross‐linking during lung development. Using a transglutaminase 2 (TGM2) knockout mouse, and cysteamine, a broad‐spectrum pharmacological inhibitor of transglutaminase activity; a causal role for TGM2 in normal lung development was noted. Additionally, cysteamine administration partially restored proper extracellular matrix structure, but not alveolar architecture, in experimental bronchopulmonary dysplasia, a disorder of lung development in newborns.